Effect of ppGpp on Escherichia coli Cyclopropane Fatty Acid Synthesis Is Mediated through the RpoS Sigma Factor (ς(S)) - Eichel, Johannes (American Society for Microbiology, 1999)
Strains of Escherichia coli carrying mutations at the relA locus are deficient in cyclopropane fatty acid (CFA) synthesis, a phospholipid modification that occurs as cultures enter stationary phase. RelA protein catalyzes the synthesis of guanosine-3′,5′-bisdiphosphate (ppGpp); therefore, ppGpp was a putative direct regulator of CFA synthesis. The nucleotide could act by increasing either the activity or the amount of CFA synthase, the enzyme catalyzing the lipid modification. We report that the effect of RelA on CFA synthesis is indirect. In vitro and in vivo experiments show no direct interaction between ppGpp and CFA synthase activity. The relA effect is due to ppGpp-engendered stimulation of the synthesis of the alternative sigma factor, RpoS, which is required for function of one of the two promoters responsible for expression of CFA synthase.